Aquaporin-4 deficiency facilitates fear memory extinction in the hippocampus through excessive activation of extrasynaptic GluN2B-containing NMDA receptors. (January 2017) - Wu, Xin; Zhang, Jie-Ting; Li, Di; Zhou, Jun; Yang, Jun; Zheng, Hui-Ling; Chen, Jian-Guo; Wang, Fang
Abstract: Aquaporin-4 (AQP-4) is the predominant water channel in the brain and primarily expressed in astrocytes. Astrocytes have been generally believed to play important roles in regulating synaptic plasticity and information processing. A growing number of evidence shows that AQP-4 plays a potential role in the regulation of astrocyte function. However, little is known about the function of AQP-4 for synaptic plasticity in the hippocampus. Therefore, we evaluated long-term depression (LTD) in the hippocampus and the extinction of fear memory of AQP-4 knockout (KO) and wild-type (WT) mice. We found that AQP-4 deficiency facilitated fear memory extinction and NMDA receptors (NMDARs)-dependent LTD in the CA3-CA1 pathway. Furthermore, AQP-4 deficiency selectively increased GluN2B-NMDAR-mediated excitatory postsynaptic currents (EPSCs). The excessive activation of extrasynaptic GluN2B-NMDAR contributed to the facilitation of NMDAR-dependent LTD and enhancement of fear memory extinction in AQP-4 KO mice. Thus, it appears that AQP-4 may be a potential target for intervention in fear memory extinction. This article is part of the Special Issue entitled 'Ionotropic glutamate receptors'. Highlights: AQP-4 deficiency facilitates fear extinction. AQP-4 deficiency facilitates NMDAR-LTD in the CA3-CA1 pathway. Excessive activation of extrasynaptic GluN2B-NMDAR contributes to the changes in AQP-4 KO mice.